Recent developments and application of bimetallic based materials in water purification - Debnath, Abhijit (Elsevier, 2021)
The shortage of clean drinking water is of great concern in many parts of the world. This problem results from a rapid population increase, defiling water resources, protracted droughts, and flooding due to climate change and anthropogenic activities. The scientific research that focuses on designing efficient materials to purify and recycle water is of paramount importance. Treatment of wastewater using traditional methods remain inefficient for providing sufficient, safe, and drinking water due to an increase in the water demand, coupled with the strict health guidelines for the level of contaminants in drinking water by the World Health Organization (WHO) and the United States Environmental Protection Agency (USEPA). Presently, highly efficient wastewater treatment is attainable due to the availability of affordable multifunctional nanomaterials. Bimetallic nanomaterials are designed by incorporating two dissimilar metals. These bimetallic materials exhibit more efficient characteristics than parental metal precursors due to the extensive array of chemical and physical properties, synergistic effects, and different mechanisms of action. This review highlights the recent developments in the synthesis and applications of bimetallic nanomaterials to remove various pollutants from water.
Keywords: Bimetal; oxide; Heavy metals; Radionuclides; Pharmaceuticals; Wastewater